2024
DOI: 10.1037/cps0000223
|View full text |Cite
|
Sign up to set email alerts
|

Your body, my experience: A systematic review of embodiment illusions as a function of and method to improve body image disturbance.

Jade Portingale,
Isabel Krug,
Hermione Liu
et al.

Abstract: Body image disturbance (BID) is a core feature of eating disorders and body dysmorphic disorder, with embodiment illusions offering the potential for understanding and treating BID through manipulating multisensory integration processes underlying self-perception. This systematic review is the first to evaluate evidence on whether (a) varying BID levels (i.e., BID-related diagnoses or higher levels of BID symptomatology) impact susceptibility to embodiment illusions and (b) embodiment illusions can improve BID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Of the 32 studies reviewed by Portingale et al. ( 48 ), only one included a non-WEIRD Asian sample, demonstrating that avatar embodiment improved body perceptions in Taiwanese individuals ( 50 ): however, this study did not assess illusion susceptibility or compare cultures. The remaining 31 reviewed studies from WEIRD samples also failed to address ethnicity or cultural factors.…”
Section: Generalisability Of Current Embodiment Illusion Research To ...mentioning
confidence: 94%
See 2 more Smart Citations
“…Of the 32 studies reviewed by Portingale et al. ( 48 ), only one included a non-WEIRD Asian sample, demonstrating that avatar embodiment improved body perceptions in Taiwanese individuals ( 50 ): however, this study did not assess illusion susceptibility or compare cultures. The remaining 31 reviewed studies from WEIRD samples also failed to address ethnicity or cultural factors.…”
Section: Generalisability Of Current Embodiment Illusion Research To ...mentioning
confidence: 94%
“…Researchers have increasingly utilised embodiment illusions to understand and improve perceptual body image disturbance in EDs and BDD (i.e., body shape/weight misestimation), which has been neglected compared to cognitive, affective, and behavioural components in current research and intervention ( 48 ). A recent systematic review by Portingale et al ( 48 ) found that individuals with higher body image disturbance were more susceptible to these illusions, indicating potential multisensory integration deficits underlying perceptual image disturbances. Embodiment illusions were also shown to update and improve disturbed body perceptions: e.g., experiencing a full-body illusion with a healthy weight model reduced body size overestimation in anorexia nervosa samples.…”
Section: Multisensory Integration Embodiment Illusions and Body Image...mentioning
confidence: 99%
See 1 more Smart Citation